New myomectomy technique for diffuse uterine leiomyomatosis. Issue 6 (June 2014) - Nishida, Masato; Ichikawa, Ryota; Arai, Yuko; Sakanaka, Miyako; Otsubo, Yasuo
Abstract Aim The aim of this study was to determine the effects of a new myomectomy technique for diffuse uterine leiomyomatosis. Material and Methods To enucleate multiple myomas, we developed a novel myomectomy technique involving longitudinal dissection of the uterus in the midline. On each side of the anterior and posterior walls, the uterine wall was further divided into two pieces from the incision site. Myomas were separated into serosal and mucosal sides, and then enucleated for removal from the thinned myometrium. Results This procedure was applied for seven patients with diffuse leiomyomatosis. The mean number of myomas enucleated from each patient was 117 (range, 74–226). Mean total weight of enucleated myomas was 147.6 g (range, 59–360 g). Mean operative time was 284 min (range, 212–407 min). Mean blood loss was 1614 g (range, 428–4421 g), with three patients requiring blood transfusion. Anemia due to menorrhagia improved in all women. Three patients became pregnant, with two undergoing cesarean section after a normal course of pregnancy and giving birth to healthy babies. The third pregnancy ended in miscarriage. We noticed intraoperatively that myoma nodules were connected to each other in every case. Conclusions This procedure should be considered as a therapeutic option in women suffering from symptoms of diffuse uterine leiomyomatosis who wish to avoid hysterectomy.